SUBFOVEAL CHOROIDAL THICKNESS AND VASCULAR DIAMETER IN ACTIVE AND RESOLVED CENTRAL SEROUS CHORIORETINOPATHY. Issue 1 (January 2018) - Chung, Yoo-Ri; Kim, Jong Wan; Choi, Shin-Young; Park, Sung Wook; Kim, Jeong Hun; Lee, Kihwang
Abstract : Purpose: To determine the subfoveal choroidal thickness and analyze Haller's layer, Sattler's layer, and large choroidal vessel diameter in eyes with active central serous chorioretinopathy (CSC) and after resolution of CSC. Methods: Ocular and clinical features of 32 eyes with CSC were analyzed retrospectively from October 2014 to September 2015. Subfoveal choroidal thickness and thicknesses of Haller's layer and Sattler's layer were measured in the active and resolved states. The diameter of the subfoveal choroidal hyporeflective lumen (i.e., the large choroidal vessel in Haller's layer) was also measured. Results: The mean subfoveal choroidal thickness, mean thickness of Haller's layer, and mean choroidal vessel diameter were significantly less after the resolution of CSC ( P < 0.001). However, the thickness of Sattler's layer did not change after the resolution of CSC ( P = 0.731). There were no significant differences among the different treatment modalities. Conclusion: After the resolution of CSC, the subfoveal choroidal thickness and thickness of Haller's layer declined, but the reduced diameter of subfoveal choroidal vessels accounted for only about half of the total thickness changes in the choroid. These results suggest that nonvascular smooth muscle cells might play a role in the thickening of the choroid during CSC and possibly in the pathogenesis and progression of CSC. Abstract : After the resolution of central serous chorioretinopathy, the subfoveal choroidal thickness and thickness of Haller's layer declined, but the reduced diameter of subfoveal choroidal vessels accounted for only about half of the total thickness changes in the choroid, suggesting the role of nonvascular smooth muscle cells.